A atuação do Montepio na produção estatal de habitação em João Pessoa de 1932 - Nunes, Angela Araújo (2008)
This work analyzes the constructive actuations of the Real Estate Portfolio of Montepio Paraiba State in the statal housing production in the city of João Pessoa, from 1932 to 1963, established between the institutional designation for the production of housing in benefit of the public functionalism and its last popular realization before the work of BNH. Through exhausting documental research, done in local collections and especially through the newspaper A União , official record of the realizations of the state executive, data was found regarding the realizations of the housings by the institution, identifying the groups of popular housing and later on classifying the built unities and the reconstitution of the house plans and the front elevation. And through the study of the introduction of these popular units and of most of the residential housings, as were called the houses that were built separately and that were not considered popular, we managed to determine the relation between the built patrimony by Montepio and the urban evolution of João Pessoa. And even without grand urbanistic plans or big aggregations as other federal institutions, the Montepio consolidated the residential use in the central region of the city, near Solon de Lucena Park; Attracted the interest of the government to the installation of infra-structure after the introduction of the cities and aggregations although the statal response took more time; it was responsible for the initial incursions in districts like Torre and Expedicionários that later on would become residential districts through the doings of other public institutions and, finally, consolidated the peripheral introduction of the statal housings with the construction of the State public employees city in the district of Oitizeiro.